A spool of blue thread - Tyler, Anne (Alfred A. Knopf, 2015)
"It was a beautiful, breezy, yellow-and-green afternoon." This is the way Abby Whitshank always begins the story of how she fell in love with Red that day in July 1959. The whole family--their two daughters and two sons, their grandchildren, even their faithful old dog--is on the porch, listening contentedly as Abby tells the tale they have heard so many times before. And yet this gathering is different too: Abby and Red are growing older, and decisions must be made about how best to look after them, and the fate of the house so lovingly built by Red's father. --